Cultural Norm Configurations in Acehnese Lullaby - Devi Pratiwy (ITScience (Information Technology and Science), 2021)
This study is aimed to provide an overview of the cultural reality of lullaby, doda idi from Acehnese family habit. This study describes the cultural norms and values configuration viewed from an ethno-pragmatic perspective and the local wisdom identified from the discourse. This study presents the cultural script approach. This approach is a descriptive technique that has grown out of the cross-cultural semantic theory proposed. The cultural discourse analysis of norms and values on natural semantic meta-language theory. It is considering that cultural norms and values constituted rules and regulations in social communication interaction practices. This lullaby linked to particular ways of speaking in the family's private domain, in this case, from mother and her child. Generally speaking, most cross-cultural communication styles assume that within a particular speech community, there are certain shared understandings about how it is appropriate to speak in a particular and cultural situation. A certain methodological technique is adopted to describe speech patterns and identify the relevant cultural values of this speech pattern. The proposed Acehnese cultural script is linked with (1) Showing high respect, (2) patriotic spirit, and (3) giving advice. The configuration of these cultural norms and values is the understanding of knowledge and wisdom in terms of the lullaby system. The configuration is constructed in low-level scripts with lexicons in semantic primes.